Protection of Appointed Children's Rights According to Law Number 35 of 2014 Concerning Child Protection - Razy, Fakhruddin (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Adoption in Indonesia is still a problem for the community, especially in matters concerning the regulations that govern it. In Indonesia, adoption has become a community need and is part of the family law system, because it involves the interests of people per person in the family. Bushar Muhammad, divides adoption into two types, namely: direct adoption (adopting children), and indirect adoption (through marriage). Law Number 35 of 2014 concerning Child Protection explicitly states that the purpose of child adoption, the motivation for adoption can only be done for the best interests of the child and carried out based on local customs and provisions of applicable laws and regulations.